PENGARUH PERSEPSI HARGA, IKLAN, DAN KETIDAKPUASAN KONSUMEN TERHADAP KEPUTUSAN BERALIH MEREK BLACKBERRY KE SAMSUNG (STUDI PADA EX PENGGUNA SMARTPHONE MEREK BLACKBERRY DI FAKULTAS EKONOMI UNISBANK KOTA SEMARANG) - Ahmad Junaidi, 12.05.51.0154; Soliha, Euis (Students Journal of Economic and Management, 2016)
Consumer brand switching is a complex phenomenon influenced by behavioral factors, competition, and time. Consumer brand switching is done due to the variation search. But the brand switching can also occur through sales promotion. Some of the things that cause dissatisfaction among consumers, advertising and the price of competitors products better and affordable for consumers. This study aims to determine the factors that influence the decision to switch brands ex Blackberry users to Samsung at the Faculty of Economics UNISBANK among other factors perception of pricing, advertising, and consumer dissatisfaction. This research is descriptive. The total sample of 100 respondents. The research instrument using a questionnaire. Analysis of data using multiple linear regression. The results showed that the perception of price is positive and significant impact on the decision to switch brands in UNISBANK Semarang. This shows that the better the perception of the price of Samsung, the decision to switch from Blackberry to Samsungs brand will increase. Advertising is positive and significant impact on the decision to switch brands in UNISBANK Semarang. This shows that the better the ads Samsung, the decision to switch from Blackberry to Samsungs brand will increase. Consumer dissatisfaction is positive and significant impact on the decision to switch brands in UNISBANK Semarang. This shows that the higher consumer dissatisfaction Blackberry hence the decision to switch from Blackberry to Samsungs brand will increase. Keywords : perception of pricing, advertising, customer dissatisfaction, decision to brands switching